Impact Of Integrating Solar PV System To Malaysian LV Network And Mitigation Using Distributed BESS - Zolkifri, Nur Izzati (2019)
The current high demand for energy and increase in greenhouse gas emission have resulted in Renewable Energy (RE) sources gaining a lot of attention in effort to sustain future energy needs. Sustainable Energy Development Authority (SEDA) data show that the most popular RE in Malaysia is solar Photovoltaic (PV) energy which has the highest installed capacity with 66.95% total installed RE. However, connection of RE into the existing distribution networks can contribute to several network problems such as voltage flicker, reverse power flow, power fluctuations in grids and unintended islanding. More specifically, solar PV system with high variability can lead to output power fluctuation. This may worsen the performance of the distribution network. In addition, it is important to maintain the flexibility and stability of the system even in the event of disturbances or sudden changes in PV generation. Thus, this research aims to investigate the impact of solar PV integration on the Malaysian distribution network under various PV integration scenarios and solar variability. Analytical method was applied to determine the Battery Energy Storage System (BESS) capacity with the aim of reducing the negative impacts of PV integration on the network. A real Malaysian network was modelled in OpenDSS software and was utilized as the reference network. It is also important to highlight that there are three scenarios in this research which indicate where the PV system was installed namely, randomly allocated PV system, concentrated PV system installation across two feeders, and unbalanced allocation of PV system. Real PV variability data obtained from weather station installed at UTeM were collected at 5-minute intervals and were utilized to study their impacts on network distribution. A corresponding size of distributed BESS was modelled to store the excessive energy during low demand and deliver it during high demand. The findings suggest that randomly allocated PV systems are suitable for PV installation in residential areas. In addition, the result for BESS installation during high PV penetration showed significant improvement on the net load profile, and this can assist utility providers to deliver more reliable power supply.